Method for producing water-absorbent resin particles, water-absorbent resin particles, absorbent body, and absorbent article

By optimizing the manufacturing method of absorbent resin particles through two or more stages of reverse suspension polymerization and surface crosslinking processes, the problem of insufficient absorbency of absorbent resin particles in absorbent products is solved, and the absorbency is improved.

CN121002072APending Publication Date: 2025-11-21SUMITOMO SEIKA CHEM CO LTD

Patent Information

Application Number
CN202480025393.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-13
Filing Date
2024-04-10
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

The absorbent properties of the superabsorbent resin particles in existing absorbent articles are insufficient, resulting in a decline in properties such as permeation rate, rewetting, and leakage. It is difficult to reduce the amount of superabsorbent resin particles and pulp used while maintaining the performance of absorbent articles.

Method used

A two-stage or higher reverse suspension polymerization method was adopted, using azo compounds as free radical polymerization initiators. The amount of internal crosslinking agent and azo compounds was controlled, and surface crosslinking was performed after polymerization to optimize the saline water retention capacity and the 5-minute value of unpressurized dry water (DW).

Benefits of technology

The saline water retention capacity of the absorbent resin particles was improved, as were the saline water absorption capacity under a load of 4.14 kPa and the 5-minute value under no-pressurization DW, thus enhancing the absorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

Provided is a novel method for producing water-absorbent resin particles with which it is possible to obtain water-absorbent resin particles having excellent high absorption performance (in particular, physiological saline water retention, physiological saline water absorption under a load of 4.14 kPa, and 5-minute value characteristics of non-pressurized DW). The method for producing water-absorbent resin particles is a method for producing water-absorbent resin particles by subjecting a water-soluble ethylenically unsaturated monomer to reversed-phase suspension polymerization using radical polymerization initiators, at least one of the radical polymerization initiators being an azo compound, the reversed-phase suspension polymerization comprising two or more polymerization steps, in the first-stage polymerization step, (a) 0.01 mmol or more and 0.11 mmol or less of an internal crosslinking agent is used with respect to 1 mol of a water-soluble ethylenically unsaturated monomer used during the first-stage polymerization; in the second-stage polymerization step, (b) 0-0.042 mmol of the internal crosslinking agent is used per 1 mol of the water-soluble ethylenically unsaturated monomer used during the second-stage polymerization, (c) 0.38 mmol or less of the azo compound is used per 1 mol of the water-soluble ethylenically unsaturated monomer used during the second-stage polymerization, and (c) 0.38 mmol or less of the azo compound is used per 1 mol of the water-soluble ethylenically unsaturated monomer used during the second-stage polymerization. A surface crosslinking step is provided after the polymerization step subsequent to the second step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for manufacturing absorbent resin particles, absorbent resin particles, absorbent bodies, and absorbent articles. More specifically, it relates to a method for manufacturing absorbent resin suitable for use in absorbent materials such as diapers, sanitary napkins, and incontinence pads, absorbent resin particles, absorbent bodies using the absorbent resin particles, and absorbent articles. Background Technology

[0002] Absorbent polymers have been widely used in recent years in the field of hygiene materials such as diapers, sanitary napkins, and incontinence pads.

[0003] As such absorbent resin particles, cross-linked polymers of water-soluble olefinic unsaturated monomers, and more specifically, cross-linked polymers of partially neutralized polyacrylic acid, have excellent water absorption capacity. Acrylic acid, as their raw material, is readily available industrially. Therefore, they have many advantages such as stable quality, low cost, and resistance to spoilage and deterioration, and are thus considered preferred absorbent resin particles (see, for example, Patent Document 1).

[0004] Absorbent products such as diapers, sanitary napkins, and incontinence pads mainly consist of an absorbent core in the center that absorbs and retains bodily fluids such as urine and menstrual blood; a liquid-permeable surface sheet (top sheet) on the side in contact with the body; and a liquid-resistant back sheet (back sheet) on the opposite side in contact with the body. Furthermore, the absorbent core is typically composed of hydrophilic fibers such as pulp and absorbent resin particles.

[0005] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 3-227301 Summary of the Invention

[0006] The technical problem that the invention aims to solve In such absorbent articles, a higher water retention capacity is required for the absorbent resin particles contained in the absorbent body. By using absorbent resin particles with high water retention capacity in absorbent articles, from the viewpoint of maintaining the overall water retention capacity of the absorbent article, it is possible to reduce, for example, the amount of absorbent resin particles and hydrophilic fibers such as pulp used in the absorbent article. However, this sometimes reduces other properties of the absorbent article (such as permeation rate, backflow, and leakage). Therefore, by improving the absorption performance of the absorbent resin particles, it is possible to reduce the amount of absorbent resin particles and hydrophilic fibers such as pulp used in the absorbent article while maintaining its performance.

[0007] The inventors of this invention, from the viewpoint of improving the absorbency of absorbent resin particles used in absorbent articles, focused on the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of demand hygroscopicity (hereinafter referred to as unpressurized DW).

[0008] In this context, the main objective of the present invention is to provide a novel method for manufacturing absorbent resin particles, which yields absorbent resin particles with excellent high absorbency (particularly characteristics of saline water retention, saline water absorption under 4.14 kPa load, and 5-minute DW value without pressurization). Furthermore, the present invention also aims to provide absorbent resin particles with excellent high absorbency (particularly characteristics of saline water retention, saline water absorption under 4.14 kPa load, and 5-minute DW value without pressurization), absorbent bodies utilizing these absorbent resin particles, and absorbent articles.

[0009] Technical solutions for solving technical problems The inventors conducted in-depth research to solve the aforementioned technical problems. The results showed that in a method for manufacturing absorbent resin particles using a free radical polymerization initiator to induce reverse suspension polymerization of water-soluble olefinic unsaturated monomers, using an azo compound as the free radical polymerization initiator and performing reverse suspension polymerization in two or more stages, and further setting the amounts of the internal crosslinking agent used in the first stage polymerization, the internal crosslinking agent used in the second stage polymerization, and the azo compound used in the second stage polymerization within specified ranges, and then performing a surface crosslinking process after polymerization, absorbent resin particles with excellent absorption properties (especially characteristics such as saline water retention, saline water absorption under a 4.14 kPa load, and 5-minute DW values ​​without pressure) can be obtained. This invention was completed based on further repeated and in-depth research based on these insights.

[0010] That is, the present invention provides an invention having the following configuration.

[0011] Item 1. A method for manufacturing water-absorbing resin particles, comprising using a free radical polymerization initiator to induce reverse suspension polymerization of water-soluble olefinic unsaturated monomers to manufacture water-absorbing resin particles. At least one of the free radical polymerization initiators is an azo compound. The reverse suspension polymerization has two or more polymerization processes. In the first stage of the polymerization process, (a) Use an internal crosslinking agent of more than 0.01 mmol and less than 0.11 mmol relative to 1 mol of water-soluble olefinic unsaturated monomer used in the first stage of polymerization; In the second stage of the polymerization process, (b) For every 1 mole of water-soluble olefinic unsaturated monomer used in the second stage of polymerization, use an internal crosslinking agent of 0 mmol to 0.042 mmol. (c) Use less than 0.38 mmol of an azo compound relative to 1 mole of water-soluble olefinic unsaturated monomer used in the second stage of polymerization; Following the polymerization process after the second stage, a surface crosslinking process is performed.

[0012] Item 2. The method for manufacturing water-absorbing resin particles according to Item 1, wherein the storage modulus of the 40-fold swollen gel formed by the primary particles obtained in the first polymerization step with ion-exchanged water is 10 Pa or more and 200 Pa or less. The storage modulus of the 40-fold swollen gel formed by the secondary particles obtained in the polymerization process after the second stage is above 5 Pa and below 200 Pa when ion-exchanged water is used.

[0013] Item 3. The method for manufacturing water-absorbing resin particles according to item 1 or 2, wherein the water-absorbing resin particles have the following characteristics (A) to (C): (A) The water retention capacity of physiological saline is above 50g / g and below 80g / g.

[0014] (B) The amount of physiological saline absorbed under a load of 4.14 kPa is more than 15 g / g and less than 40 g / g.

[0015] (C) The 5-minute value of DW without pressurization is above 50 mL / g and below 80 mL / g.

[0016] Item 4. A water-absorbing resin particle, which is a cross-linked polymer of a water-soluble olefinically unsaturated monomer. The absorbent resin particles have the following characteristics (A) to (C): (A) The water retention capacity of physiological saline is above 50g / g and below 80g / g.

[0017] (B) The amount of physiological saline absorbed under a load of 4.14 kPa is more than 15 g / g and less than 40 g / g.

[0018] (C) The 5-minute value of DW without pressurization is above 50 mL / g and below 80 mL / g.

[0019] Item 5. An absorbent comprising the water-absorbing resin particles described in Item 4.

[0020] Item 6. An absorbent article comprising the absorbent described in item 5.

[0021] Invention Effects According to the present invention, a novel method for manufacturing absorbent resin particles is provided, which yields absorbent resin particles with excellent absorption properties (particularly characteristics of saline water retention, saline water absorption under 4.14 kPa load, and 5-minute values ​​without pressurization). Furthermore, according to the present invention, absorbent resin particles with excellent absorption properties (particularly characteristics of saline water retention, saline water absorption under 4.14 kPa load, and 5-minute values ​​without pressurization), absorbent bodies utilizing the absorbent resin particles, and absorbent articles are also provided. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of a measuring apparatus for measuring the pressureless DW of water-absorbing resin particles.

[0023] Figure 2 This is a schematic diagram of a measuring device used to determine the amount of water absorbed by physiological saline from absorbent resin particles under a load of 4.14 kPa. Detailed Implementation

[0024] In this specification, "comprising" means both "consisting essentially of" and "consisting of". Additionally, in this specification, "(meth)acrylic acid" means "acrylic acid or methacrylic acid", "(meth)acrylate / salt" means "acrylate / salt or methacrylate / salt", and "(poly)" refers to both the presence and absence of the prefix "poly". Furthermore, in this specification, "water solubility" means a solubility of 5% by mass or more in water at 25°C.

[0025] In this specification, the value connected by "~" refers to the range of values ​​before and after "~" as the lower and upper limits. When multiple lower and upper limits are specified separately, any lower and upper limits can be selected and connected by "~".

[0026] 1. Method for manufacturing water-absorbing resin particles The method for manufacturing the superabsorbent resin particles of the present invention involves using a free radical polymerization initiator to induce a reverse suspension polymerization of water-soluble olefinically unsaturated monomers to produce superabsorbent resin particles. At least one of the free radical polymerization initiators is an azo compound. In the method for manufacturing the superabsorbent resin particles of the present invention, the reverse suspension polymerization comprises two or more polymerization steps.

[0027] In the method for manufacturing the water-absorbing resin particles of the present invention, in the first stage of the reverse suspension polymerization process, (a) an internal crosslinking agent is used at a concentration of 0.01 mmol or more and 0.11 mmol or less relative to 1 mole of the water-soluble olefinic unsaturated monomer used in the first stage polymerization. Furthermore, in the second stage polymerization process, (b) an internal crosslinking agent is used at a concentration of 0 mmol or more and 0.042 mmol or less relative to 1 mole of the water-soluble olefinic unsaturated monomer used in the second stage polymerization, and (c) an azo compound is used at a concentration of 0.38 mmol or less relative to 1 mole of the water-soluble olefinic unsaturated monomer used in the second stage polymerization. Moreover, the method for manufacturing the water-absorbing resin particles of the present invention includes a surface crosslinking step after the polymerization steps following the second stage.

[0028] The method for manufacturing the absorbent resin particles of the present invention, by having these components, enables the production of absorbent resin particles with excellent absorption performance (particularly characteristics of saline water retention, saline water absorption under 4.14 kPa load, and 5-minute values ​​without pressurization DW). The method for manufacturing the absorbent resin particles of the present invention will be described in detail below.

[0029] [Reverse suspension polymerization] In reverse suspension polymerization, for example, an aqueous solution of a monomer containing a water-soluble olefinically unsaturated monomer is dispersed in a dispersion medium in the presence of a dispersing stabilizer. As described later, a hydrocarbon dispersion medium is preferred, for example.

[0030] Conventionally, when obtaining superabsorbent resin particles by reverse suspension polymerization of water-soluble olefinically unsaturated monomers, reverse suspension polymerization can be performed in a single-stage polymerization process. However, the reverse suspension polymerization in this invention involves multiple stages, including two or more. From the viewpoint of maximizing the effects of this invention while improving the productivity of superabsorbent resin particles, reverse suspension polymerization is preferably performed in two to three stages.

[0031] In reverse suspension polymerization, after the first stage of polymerization (first-stage reverse suspension polymerization), a water-soluble olefinic unsaturated monomer can be added to and mixed in the reaction mixture obtained from the first-stage polymerization reaction, and subsequent polymerization stages (first-stage reverse suspension polymerization) can be carried out using the same method as the first stage. In each subsequent stage of reverse suspension polymerization, preferably, in addition to the water-soluble olefinic unsaturated monomer, a predetermined amount of polymerization initiator is added based on the amount of water-soluble olefinic unsaturated monomer added during each subsequent stage of reverse suspension polymerization. It should be noted that, in the polymerization after the second stage, an internal crosslinking agent may also be added to the water-soluble olefinic unsaturated monomer as needed.

[0032] Additionally, as described later, in reverse suspension polymerization, a dispersing stabilizer (surfactant, polymeric dispersant) is also preferred. If the polymerization reaction is to begin, the dispersing stabilizer can be added either before or after the monomer aqueous solution is added.

[0033] From the viewpoint of easily reducing the amount of residual hydrocarbon dispersion medium in the obtained water-absorbing resin particles, it is preferable to polymerize the monomer aqueous solution in a hydrocarbon dispersion medium in which a polymeric dispersant is dispersed, and then to disperse the surfactant.

[0034] From the viewpoint of enabling rapid polymerization, shortening polymerization time, thereby improving economy, and easily removing the heat of polymerization to ensure smooth reaction, the reaction temperature is preferably 20 to 110°C, and more preferably 40 to 90°C.

[0035] <Polymerization Process> In each polymerization step after the first and second stages, water-soluble olefinic unsaturated monomers are polymerized using reverse suspension polymerization with a free radical polymerization initiator. Specifically, an aqueous solution containing water-soluble olefinic unsaturated monomers, a hydrocarbon dispersion medium, a free radical polymerization initiator, and an internal crosslinking agent are mixed to carry out the polymerization reaction of the water-soluble olefinic unsaturated monomers.

[0036] In this invention, during the first stage of polymerization, (a) an internal crosslinking agent is used at a concentration of 0.01 mmol or more and 0.11 mmol or less relative to 1 mole of the water-soluble olefinic unsaturated monomer used in the first stage of polymerization. Furthermore, in this invention, during the second stage of polymerization, (b) an internal crosslinking agent is used at a concentration of 0 mmol or more and 0.042 mmol or less relative to 1 mole of the water-soluble olefinic unsaturated monomer used in the second stage of polymerization, and (c) an azo compound is used at a concentration of 0.38 mmol or less relative to 1 mole of the water-soluble olefinic unsaturated monomer used in the second stage of polymerization.

[0037] The following details each polymerization process after the first and second stages.

[0038] [Water-soluble olefinic unsaturated monomers] Examples of water-soluble olefinically unsaturated monomers include (meth)acrylic acid and its salts; 2-(meth)acrylamide-2-methylpropanesulfonic acid and its salts; nonionic monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, (meth)acrylic acid-2-hydroxyethyl ester, N-hydroxymethyl(meth)acrylamide, and polyethylene glycol mono(meth)acrylamide; and amino-containing unsaturated monomers and their quaternaries, such as N,N-diethylaminoethyl(meth)acrylamide, N,N-diethylaminopropyl(meth)acrylamide, and diethylaminopropyl(meth)acrylamide. From the viewpoint of easy industrial availability, (meth)acrylic acid or its salts, (meth)acrylamide, and N,N-dimethylacrylamide are preferred, and (meth)acrylic acid and its salts are more preferred. It should be noted that these water-soluble olefinically unsaturated monomers can be used alone or in combination of two or more.

[0039] Acrylic acid and its salts have been widely used as raw materials for water-absorbing resin particles. These acrylic acids and / or their salts are sometimes copolymerized with other water-soluble olefinic unsaturated monomers. In this invention, the content of the water-soluble olefinic unsaturated monomers, specifically acrylic acid and its salts, is 70–100 mol%. That is, the proportion of acrylic acid and its salts in the total water-soluble olefinic unsaturated monomers is 70–100 mol.

[0040] Water-soluble olefinic unsaturated monomers are dispersed in a hydrocarbon dispersion medium in an aqueous solution for reverse suspension polymerization. The formation of an aqueous solution by the water-soluble olefinic unsaturated monomers improves their dispersion efficiency in the hydrocarbon dispersion medium. The concentration of the water-soluble olefinic unsaturated monomers in this aqueous solution is preferably in the range of 20% by mass to below the saturation concentration.

[0041] The concentration of the water-soluble olefinic unsaturated monomer during the first stage of polymerization is preferably 55% by mass or less, more preferably 50% by mass or less, and even more preferably 45% by mass or less, from the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization. On the other hand, the concentration of the water-soluble olefinic unsaturated monomer is preferably 25% by mass or more, more preferably 30% by mass or more, and even more preferably 35% by mass or more, from the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization.

[0042] The concentration of the water-soluble olefinic unsaturated monomer during the second-stage polymerization is preferably 55% by mass or less, more preferably 50% by mass or less, and even more preferably 45% by mass or less, from the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization. On the other hand, the concentration of the water-soluble olefinic unsaturated monomer is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, from the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization.

[0043] The ratio of the amount of water-soluble olefinic unsaturated monomer used in the second stage of polymerization to the amount of water-soluble olefinic unsaturated monomer used in the first stage of polymerization (amount used in the second stage / amount used in the first stage) is preferably 0.1 to 3.0, more preferably 0.5 to 2.5, further preferably 1.0 to 2.0, and even more preferably 1.3 to 1.5, from the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization.

[0044] Water-soluble olefinically unsaturated monomers can be obtained by pre-neutralizing their acid groups (the acid groups of acrylic acid) with an alkaline neutralizing agent, as needed. Examples of such alkaline neutralizing agents include alkali metal salts such as sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, and potassium carbonate; and ammonia. Furthermore, for ease of neutralization, these alkaline neutralizing agents can be used in aqueous solution form. It should be noted that the above-mentioned alkaline neutralizing agents can be used alone or in combination of two or more.

[0045] From the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressure, the degree of neutralization of the water-soluble olefinic unsaturated monomer using an alkaline neutralizing agent is preferably 10 to 100 mol%, more preferably 30 to 90 mol%, even more preferably 50 to 85 mol%, and even more preferably 70 to 80 mol%.

[0046] [Polymerization initiator] The polymerization initiators mixed in the polymerization process are free radical polymerization initiators, and at least one of them is an azo compound.

[0047] Azo compounds can also be used alone as free radical polymerization initiators. From the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization, it is preferable to use azo compounds and peroxides together.

[0048] The use of both peroxides and azo compounds does not necessarily mean that the azo compounds and peroxides must coexist at the start of the polymerization reaction. Rather, it means that the other compound is already present when the monomer conversion caused by the free radical cleavage of one compound is less than 10%. However, it is preferable that both coexist in an aqueous solution containing water-soluble olefinic unsaturated monomers before the start of the polymerization reaction. Furthermore, the azo compounds and peroxides can be added to the polymerization reaction system through their respective flow paths, or sequentially through the same flow path.

[0049] It should be noted that the azo compounds and peroxides used can be in the form of powder or aqueous solution.

[0050] Examples of peroxides include persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate; and peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, di-tert-butyl peroxide, tert-butyl cumene peroxide, tert-butyl peracetate, tert-butyl perisobutyrate, tert-butyl perpentyl peroxide, and hydrogen peroxide. Among these peroxides, potassium persulfate, ammonium persulfate, and sodium persulfate are preferred from the viewpoint of ease of acquisition and handling.

[0051] From the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressure, the amount of peroxide used in the first stage of polymerization is preferably 0.001 to 1.0 mmol, more preferably 0.01 to 0.50 mmol, further preferably 0.05 to 0.30 mmol, and even more preferably 0.075 to 0.15 mmol, relative to 1 mole of water-soluble olefinic unsaturated monomer used in the first stage of polymerization.

[0052] From the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization, the amount of peroxide used in the second stage of polymerization is preferably 0.001 to 1.0 mmol, more preferably 0.01 to 0.50 mmol, further preferably 0.05 to 0.20 mmol, and even more preferably 0.075 to 0.15 mmol, relative to 1 mole of water-soluble olefinic unsaturated monomer used in the second stage of polymerization.

[0053] In addition, examples of azo compounds include: 2,2′-azobis(2-amidinylpropane) dihydrochloride, 2,2′-azobis[2-(N-phenylamidinyl)propane] dihydrochloride, 2,2′-azobis[2-(N-allylamidinyl)propane] dihydrochloride, 2,2′-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane} dihydrochloride, 2,2′-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propamide}, 2,2′-azobis[2-methyl-N-(2-hydroxyethyl)-propamide], and 4,4′-azobis(4-cyanopentanoic acid). Among these azo compounds, 2,2′-azobis(2-amidinylpropane) dihydrochloride is preferred from the viewpoint of being easy to obtain and manipulate.

[0054] The amount of azo compound used in the first stage of polymerization is preferably 0 to 1.0 mmol, more preferably 0 to 0.50 mmol, further preferably 0.10 to 0.38 mmol, and even more preferably 0.20 to 0.35 mmol, relative to 1 mole of water-soluble olefinic unsaturated monomer used in the first stage of polymerization, from the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization, relative to 1 mole of water-soluble olefinic unsaturated monomer used in the first stage of polymerization.

[0055] In the manufacturing method of the present invention, (c) an azo compound of 0.38 mmol or less is used relative to 1 mole of the water-soluble olefinic unsaturated monomer used in the second stage polymerization. From the viewpoint of improving the saline water retention, saline water absorption under a 4.14 kPa load, and the 5-minute value of the unpressurized DW, the amount of the azo compound used in the second stage polymerization is preferably 0 to 0.35 mmol, more preferably 0.05 to 0.35 mmol, and even more preferably 0.10 to 0.35 mmol, relative to 1 mole of the water-soluble olefinic unsaturated monomer used in the second stage polymerization.

[0056] It should be noted that polymerization initiators can also be used in combination with reducing agents such as sodium sulfite, sodium bisulfite, ferrous sulfate, and L-ascorbic acid as redox polymerization initiators.

[0057] From the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization, the molar ratio of peroxide to azo compound during the first stage of polymerization (peroxide / azo compound) is preferably in the range of 0.1 to 1.0, more preferably in the range of 0.2 to 0.5, and even more preferably in the range of 0.3 to 0.4.

[0058] From the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressure, the molar ratio of peroxide to azo compound during the second stage of polymerization (peroxide / azo compound) is preferably in the range of 0.1 to 1.5, more preferably in the range of 0.2 to 1.0, and even more preferably in the range of 0.3 to 0.7.

[0059] [Internal cross-linking agent] As internal crosslinking agents, examples include those capable of crosslinking polymers containing water-soluble olefinically unsaturated monomers. Examples include: unsaturated polyesters obtained by reacting diols and triols such as polyethylene glycol, polypropylene glycol, 1,4-butanediol, trimethylolpropane, and polyglycerol with unsaturated acids such as methacrylic acid, maleic acid, and fumaric acid; bisacrylamides such as N,N-methylenebisacrylamide; di(meth)acrylates or tri(meth)acrylates obtained by reacting polyepoxides with methacrylic acid; and those that react toluene... Di(meth)acrylate carbamoyl esters obtained by reacting polyisocyanates such as diisocyanate and hexamethylene diisocyanate with hydroxyethyl methacrylate; compounds with two or more polymerizable unsaturated groups such as allyl starch, allylated cellulose, diallyl phthalate, N,N′,N′′-triallyl isocyanurate, and divinylbenzene; diglycidyl compounds such as polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polyglycerol diglycidyl ether; and polyglycidyl compounds such as triglycidyl compounds; epichlorohydrin and epibromohydrin. α Compounds with two or more reactive functional groups, such as epihalohydrins like methylepimercohydrin; isocyanates like 2,4-toluene diisocyanate and hexamethylene diisocyanate; and oxetane compounds such as 3-methyl-3-hydroxymethyloxetane, 3-ethyl-3-hydroxymethyloxetane, 3-butyl-3-hydroxymethyloxetane, 3-methyl-3-hydroxyethyloxetane, 3-ethyl-3-hydroxyethyloxetane, and 3-butyl-3-hydroxyethyloxetane. Among these internal crosslinking agents, unsaturated polyesters or polyglycidyl compounds are preferred, diglycidyl ether compounds are more preferred, and (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerol diglycidyl ether are particularly preferred. These internal crosslinking agents can be used alone or in combination of two or more.

[0060] In this invention, during the first stage of polymerization, (a) an internal crosslinking agent is used at a rate of 0.01 mmol to 0.11 mmol relative to 1 mol of the water-soluble olefinic unsaturated monomer used in the first stage of polymerization. From the viewpoint of improving the saline water retention, saline water absorption under a 4.14 kPa load, and the 5-minute value of the unpressurized DW, the amount of internal crosslinking agent used in the first stage of polymerization is preferably 0.02 to 0.09 mmol relative to 1 mol of the water-soluble olefinic unsaturated monomer used in the first stage of polymerization, more preferably 0.03 to 0.075 mmol, and even more preferably 0.04 to 0.6 mmol.

[0061] Furthermore, in this invention, during the second-stage polymerization process, (b) an internal crosslinking agent is used at a rate of 0 mmol to 0.042 mmol, relative to 1 mol of the water-soluble olefinic unsaturated monomer used in the second-stage polymerization. From the viewpoint of improving the saline water retention capacity, the saline water absorption capacity under a 4.14 kPa load, and the 5-minute value of the unpressurized DW, the amount of internal crosslinking agent used in the second-stage polymerization is preferably 0 to 0.038 mmol, more preferably 0 to 0.032 mmol, even more preferably 0 to 0.030 mmol, and particularly preferably 0 to 0.025 mmol, relative to 1 mol of the water-soluble olefinic unsaturated monomer used in the second-stage polymerization.

[0062] [Hydrocarbon Dispersion Medium] Examples of hydrocarbon dispersion media include: aliphatic hydrocarbons with 6 to 8 carbon atoms such as n-hexane, n-heptane, 2-methylhexane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, and n-octane; alicyclic hydrocarbons such as cyclohexane, methylcyclohexane, cyclopentane, methylcyclopentane, trans-1,2-dimethylcyclopentane, cis-1,3-dimethylcyclopentane, and trans-1,3-dimethylcyclopentane; and aromatic hydrocarbons such as benzene, toluene, and xylene. Among these hydrocarbon dispersion media, n-hexane, n-heptane, and cyclohexane are particularly suitable from the viewpoint of being readily available industrially, having stable quality, and being inexpensive. These hydrocarbon dispersion media can be used alone or in combination of two or more. It should be noted that, as an example of a mixture of hydrocarbon dispersion media, suitable results can also be obtained using commercially available products such as Exxsol heptane (manufactured by Exxon Mobil: containing 75-85% by mass of heptane and its isomers).

[0063] From the viewpoint of uniformly dispersing the water-soluble olefinic unsaturated monomer and easily controlling the polymerization temperature, the amount of water-soluble olefinic unsaturated monomer used as the hydrocarbon dispersion medium is preferably 100 to 1500 parts by mass, more preferably 150 to 1000 parts by mass, further preferably 200 to 500 parts by mass, and even more preferably 300 to 400 parts by mass, relative to 100 parts by mass of the water-soluble olefinic unsaturated monomer in the first stage.

[0064] [Dispersion stabilizer] (surfactant) In reverse suspension polymerization, a dispersion stabilizer can be used as needed to improve the dispersion stability of water-soluble olefinic unsaturated monomers in a hydrocarbon dispersion medium. Surfactants can be used as such dispersion stabilizers.

[0065] As surfactants, examples include: sucrose fatty acid esters, polyglycerol fatty acid esters, dehydrated sorbitan fatty acid esters, polyoxyethylene dehydrated sorbitan fatty acid esters, polyoxyethylene glycerol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkylallyl formaldehyde condensation polyoxyethylene ethers, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropylene alkyl ethers, polyethylene glycol fatty acid esters, alkyl glucosides, N-alkyl glucosamides, polyoxyethylene fatty acid amides, polyoxyethylene alkylamines, phosphate esters of polyoxyethylene alkyl ethers, and phosphate esters of polyoxyethylene alkylallyl ethers. Among these surfactants, dehydrated sorbitan fatty acid esters, polyglycerol fatty acid esters, and sucrose fatty acid esters are preferred, especially from the perspective of monomer dispersion stability. These surfactants can be used alone or in combination of two or more.

[0066] The amount of surfactant used is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of the water-soluble olefinic unsaturated monomer in the first stage, more preferably 0.3 to 10 parts by mass, even more preferably 0.5 to 1 part by mass, and even more preferably 0.6 to 0.9 parts by mass.

[0067] (Polymer dispersant) In addition, as a dispersant stabilizer used in reverse suspension polymerization, it can be used together with the surfactants mentioned above and with a polymeric dispersant.

[0068] Examples of polymeric dispersants include: maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified EPDM (ethylene-propylene-diene terpolymer), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethyl cellulose, and ethyl hydroxyethyl cellulose. Among these polymeric dispersants, particularly from the perspective of monomer dispersion stability, maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, and oxidized ethylene-propylene copolymer are preferred. These polymeric dispersants can be used alone or in combination of two or more.

[0069] The amount of polymeric dispersant used is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of the water-soluble olefinic unsaturated monomer in the first stage, more preferably 0.3 to 10 parts by mass, even more preferably 0.5 to 1 part by mass, and even more preferably 0.6 to 0.9 parts by mass.

[0070] [Other ingredients] In the manufacturing method of water-absorbent resin particles, other components can be added to an aqueous solution containing water-soluble olefinically unsaturated monomers as needed to carry out reverse-phase suspension polymerization. Various additives such as thickeners and chain transfer agents can be added as these other components.

[0071] (Thickener) For example, a thickener can be added to an aqueous solution containing a water-soluble olefinically unsaturated monomer to carry out reverse suspension polymerization. By adjusting the viscosity of the aqueous solution by adding a thickener, the median particle size obtained in reverse suspension polymerization can be controlled.

[0072] As thickeners, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, carboxymethyl cellulose, polyacrylic acid, partially neutralized polyacrylic acid, polyethylene glycol, polyacrylamide, polyethyleneimine, dextrin, sodium alginate, polyvinyl alcohol, polyvinylpyrrolidone, and polyethylene oxide can be used. It should be noted that if the stirring speed during polymerization is the same, there is a tendency for the viscosity of the aqueous solution of the water-soluble olefinically unsaturated monomer to be higher, and the primary and / or secondary particles of the resulting particles to be larger.

[0073] (Chain transfer agent) For example, from the viewpoint of increasing the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressure, the polymerization of water-soluble olefinic unsaturated monomers can be carried out in the presence of a chain transfer agent.

[0074] Examples of chain transfer agents include: thiols such as ethanethiol, propanethiol, and dodecanethiol; thioglycolic acids such as mercaptoacetic acid, thiomalic acid, dimethyl dithiocarbamate, diethyl dithiocarbamate, or their salts; secondary alcohols such as isopropanol; phosphorous compounds such as the normal salts of phosphorous acid such as sodium phosphorous acid, disodium phosphite, dipotassium phosphite, and diammonium phosphite, and the acid salts of phosphorous acid such as sodium hydrogen phosphite, potassium hydrogen phosphite, and ammonium hydrogen phosphite; phosphoric acid compounds such as the normal salts of phosphoric acid such as phosphoric acid, sodium phosphate, potassium phosphate, and ammonium phosphate, and the acid salts of phosphoric acid such as sodium dihydrogen phosphate, potassium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, and diammonium hydrogen phosphate; hypophosphite compounds such as hypophosphite, sodium hypophosphite, potassium hypophosphite, and ammonium hypophosphite; pyrophosphite, tripolyphosphite, polyphosphite, and their salts; trimethyl phosphate, and nitrotrimethylene triphosphoic acid. These chain transfer agents can be used alone or in combination of two or more. In addition, its hydrates can also be used as chain transfer agents.

[0075] The amount of chain transfer agent used during the second-stage polymerization is preferably 0 to 0.0005 moles relative to 1 mole of water-soluble olefinic unsaturated monomer, more preferably 0 to 0.0003 moles, further preferably 0 to 0.0002 moles, and even more preferably 0 to 0.0001 moles, from the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization.

[0076] As described above, the inventors of this invention, from the viewpoint of improving the absorbency of absorbent resin particles used in absorbent articles, focused on the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute DW value without pressure. To improve the 5-minute DW value without pressure, it is necessary to increase the surface area of ​​the absorbent resin particles. To increase the surface area of ​​the absorbent resin particles, the inventors of this invention discovered that in a method for manufacturing absorbent resin particles by reverse suspension polymerization of water-soluble olefinic unsaturated monomers, performing reverse suspension polymerization through two or more polymerization steps increases the storage modulus of the primary particles obtained in the first polymerization step and suppresses the aggregation of secondary particles obtained in subsequent polymerization steps. This results in a larger surface area of ​​the absorbent resin particles obtained by cross-linking the surfaces of the secondary particles, thus improving the 5-minute DW value without pressure. To improve the storage modulus of the primary particles obtained in the first polymerization step, it is necessary to increase the degree of cross-linking of the primary particles. However, if the degree of cross-linking of the primary particles increases, it leads to a decrease in the water retention capacity of physiological saline and the water absorption capacity of physiological saline under a load of 4.14 kPa.

[0077] Based on the above viewpoints, in this invention, the storage modulus of the 40-fold swollen gel formed by the primary particles obtained in the first-stage polymerization process using ion-exchanged water is preferably set to a range of 10 Pa or more and 200 Pa or less. From the viewpoint of improving the 5-minute value of unpressurized dry water (DW), this storage modulus is preferably 10 Pa or more, more preferably 15 Pa or more, and even more preferably 20 Pa or more. Furthermore, from the viewpoint of improving the water retention capacity of physiological saline and the water absorption capacity of physiological saline under a load of 4.14 kPa, this storage modulus is preferably 200 Pa or less, more preferably 150 Pa or less, and even more preferably 100 Pa or less. From the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of unpressurized dry water (DW), this storage modulus can be preferably in the range of 15 to 150 Pa, and more preferably in the range of approximately 20 to 100 Pa. The storage modulus can be adjusted, for example, by adjusting the amount of internal crosslinking agent used, the concentration of water-soluble olefinic unsaturated monomers, the degree of neutralization of water-soluble olefinic unsaturated monomers, and the amount of polymerization initiator used in the first-stage polymerization process. This storage modulus is measured using a stress-controlled rheometer at 25°C for primary particles obtained in the first-stage polymerization process that have been dried and then swollen 40 times with ion-exchanged water to form a 40-fold swollen gel. The specific measurement of this storage modulus utilizes the measurement method described in the examples.

[0078] Furthermore, in this invention, the storage modulus of the 40-fold swollen gel formed by the secondary particles obtained in the polymerization process after the second stage with ion-exchanged water is preferably set to a range of 5 Pa or more and 200 Pa or less. From the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressure, this storage modulus is preferably 5 Pa or more, more preferably 20 Pa or more, and even more preferably 30 Pa or more. In addition, it is preferably 200 Pa or less, more preferably 190 Pa or less, even more preferably 170 Pa or less, even more preferably 150 Pa or less, and particularly preferably 100 Pa or less. Examples of preferred ranges include 20 to 190 Pa, more preferably 20 to 170 Pa, even more preferably 30 to 150 Pa, and even more preferably around 30 to 100 Pa. The storage modulus can be adjusted, for example, by adjusting the amount of internal crosslinking agent, the concentration of water-soluble olefinic unsaturated monomer, the ratio of the amount of water-soluble olefinic unsaturated monomer used in the second-stage polymerization process to that used in the first-stage polymerization process, the degree of neutralization of the water-soluble olefinic unsaturated monomer, the amount of polymerization initiator, and the amount of chain transfer agent used in subsequent polymerization processes. This storage modulus is measured using a stress-controlled rheometer at 25°C for secondary particles obtained in the second-stage polymerization process that have been dried and then swollen 40 times using ion-exchanged water to form a 40-fold swollen gel. The specific measurement of this storage modulus utilizes the measurement method described in the examples.

[0079] From the viewpoint of more effectively utilizing the effects of the present invention, the ratio of the energy storage modulus of the secondary particles to the energy storage modulus of the primary particles (energy storage modulus of the secondary particles / energy storage modulus of the primary particles) is preferably 10 times or less, more preferably 5 times or less, and even more preferably 3 times or less; examples of preferred ranges include 0.1 to 5 times, and examples of more preferred ranges include 0.5 to 3 times, etc.

[0080] As described above, to improve the 5-minute DW value without pressure, it is necessary to increase the surface area of ​​the superabsorbent polymer (SAP) particles. To increase the surface area of ​​the SAP particles, the inventors of this invention discovered that in a method for manufacturing SAP particles by reverse suspension polymerization of water-soluble olefinic unsaturated monomers, performing reverse suspension polymerization through two or more polymerization steps increases the storage modulus of the primary particles obtained in the first polymerization step and suppresses the aggregation of secondary particles obtained in subsequent polymerization steps. This results in a larger surface area of ​​the SAP particles obtained by crosslinking the surfaces of the secondary particles, thus improving the 5-minute DW value without pressure. However, to improve the storage modulus of the primary particles obtained in the first polymerization step, it is necessary to increase the degree of crosslinking of the primary particles. If the degree of crosslinking of the primary particles is high, a decrease in the saline water retention capacity and the saline water absorption capacity under a 4.14 kPa load occurs. In contrast, it can be considered that in the method for manufacturing the water-absorbing resin particles of the present invention, by reducing the degree of internal crosslinking formed during polymerization after the second stage, the storage modulus of the secondary particles supplied before surface crosslinking is reduced, and the contribution of surface crosslinking is increased, thereby obtaining water-absorbing resin particles with excellent properties such as saline water retention, saline water absorption under a load of 4.14 kPa, and 5-minute DW value without pressure.

[0081] <Surface crosslinking (post-crosslinking) process> The surface crosslinking process is a polymerization step following the second stage of reverse suspension polymerization, in which secondary particles (hydrogel-like substances with internal crosslinking structures) obtained by polymerizing water-soluble olefinically unsaturated monomers are surface-crosslinked. The water-absorbing resin particles of the present invention are obtained by mixing the secondary particles obtained in the polymerization step with a surface crosslinking agent and then crosslinking the secondary particles (surface crosslinking reaction). This surface crosslinking reaction is preferably carried out in the presence of the surface crosslinking agent after the polymerization of the water-soluble olefinically unsaturated monomers is completed. In the present invention, primary particles and secondary particles are prepared, and then a surface crosslinking reaction is performed on the secondary particles, thereby obtaining water-absorbing resin particles with improved properties such as saline water retention, saline water absorption under a 4.14 kPa load, and the 5-minute DW value without pressure.

[0082] From the viewpoint of improving the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization, in the surface crosslinking process, the molar ratio of the surface crosslinking agent to the water-soluble olefinic unsaturated monomer (surface crosslinking agent / water-soluble olefinic unsaturated monomer) is preferably in the range of 0.00001 to 0.001, more preferably in the range of 0.00005 to 0.00080, further preferably in the range of 0.00010 to 0.00060, and even more preferably in the range of 0.00020 to 0.00040.

[0083] Compounds having two or more reactive functional groups can be cited as surface crosslinking agents. Examples include: ethylene glycol, propylene glycol, 1,4-butanediol, trimethylolpropane, glycerol, polyethylene glycol, polypropylene glycol, polyglycerol, and other polyglycerols; poly(poly)ethylene glycol diglycidyl ether, (poly)glycerol diglycidyl ether, (poly)glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, (poly)propylene glycol polyglycidyl ether, (poly)glycerol polyglycidyl ether, and other polyglycidyl compounds; epichlorohydrin, epibromohydrin, etc. α -Halogenated epoxy compounds such as methylepoxide; isocyanate compounds such as 2,4-toluene diisocyanate and hexamethylene diisocyanate; oxacyclobutane compounds such as 3-methyl-3-hydroxymethyloxacyclobutane, 3-ethyl-3-hydroxymethyloxacyclobutane, 3-butyl-3-hydroxymethyloxacyclobutane, 3-methyl-3-hydroxyethyloxacyclobutane, 3-ethyl-3-hydroxyethyloxacyclobutane, 3-butyl-3-hydroxyethyloxacyclobutane; oxacyclobutane compounds such as 1,2-ethylidene bis(oxazoline); carbonate compounds such as ethylene carbonate; bis[N,N-di( β Hydroxyalkylamide compounds such as [-hydroxyethyl]hexamethylenediamide. Among these surface crosslinking agents, polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)glycerol diglycidyl ether, (poly)glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and (poly)glycerol polyglycidyl ether are preferred. These surface crosslinking agents can be used alone or in combination of two or more.

[0084] As a method of adding surface crosslinking agents, the surface crosslinking agent can be added as is or added in an aqueous solution, or it can be added as needed as a solution using a hydrophilic organic solvent. Examples of hydrophilic organic solvents include: lower alcohols such as methanol, ethanol, n-propanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as diethyl ether, dioxane, and tetrahydrofuran; amides such as N,N-dimethylformamide; and sulfoxides such as dimethyl sulfoxide. These hydrophilic organic solvents can be used alone, in combination of two or more, or as a mixed solvent with water.

[0085] The surface crosslinking agent can be added once the polymerization reaction of the water-soluble olefinic unsaturated monomer is almost completely completed. It is preferably added in the presence of 1 to 400 parts by mass of water relative to 100 parts by mass of the water-soluble olefinic unsaturated monomer, more preferably in the presence of 5 to 100 parts by mass of water, even more preferably in the presence of 10 to 50 parts by mass of water, and even more preferably in the presence of 15 to 35 parts by mass of water. It should be noted that the amount of water refers to the total amount of water contained in the reaction system and the water required for adding the surface crosslinking agent.

[0086] The reaction temperature for the surface crosslinking reaction is preferably 50–250°C, more preferably 60–180°C, even more preferably 60–140°C, and still more preferably 70–120°C. The reaction time for the surface crosslinking reaction is preferably 1–300 minutes, more preferably 5–200 minutes.

[0087] <Drying Process> After the aforementioned reverse suspension polymerization, a drying step can be included, in which water and hydrocarbon dispersion media are removed by distillation using energy such as heat applied from the outside. When dehydrating the hydrogel after reverse suspension polymerization, the system containing the hydrogel dispersed in the hydrocarbon dispersion media is heated, thereby temporarily removing water and the hydrocarbon dispersion media from the system by azeotropic distillation. At this time, if only the distilled hydrocarbon dispersion media is returned to the system, continuous azeotropic distillation can be performed. In this case, the temperature within the drying system is maintained below the azeotropic temperature with the hydrocarbon dispersion media, which is preferable from the viewpoint of minimizing resin degradation. Next, water and the hydrocarbon dispersion media are removed by distillation to obtain water-absorbing resin particles. By controlling the processing conditions of this post-polymerization drying step and adjusting the amount of dehydration, the various properties of the obtained water-absorbing resin particles can be controlled.

[0088] In the drying process, drying by distillation can be carried out under atmospheric pressure or under reduced pressure. Alternatively, from the viewpoint of improving drying efficiency, it can also be carried out under a gas stream such as nitrogen. When drying is carried out under atmospheric pressure, the preferred drying temperature is 70–250°C, more preferably 80–180°C, even more preferably 80–140°C, and still more preferably 90–130°C. When drying is carried out under reduced pressure, the preferred drying temperature is 40–160°C, more preferably 50–110°C.

[0089] It should be noted that when a surface crosslinking step using a surface crosslinking agent is performed after monomer polymerization via reverse suspension polymerization, the aforementioned drying step using distillation is performed after the surface crosslinking step is completed. Alternatively, the surface crosslinking step and the drying step can be performed simultaneously.

[0090] The absorbent resin particles obtained by the manufacturing method of the present invention may contain additives depending on the intended use. Examples of such additives include inorganic powders, surfactants, oxidizing agents, reducing agents, metal chelating agents, free radical chain inhibitors, antioxidants, and antibacterial agents. For example, inorganic powders may be used to further improve the flowability of the absorbent resin particles. The amount of inorganic powder used is preferably in the range of 0.01 to 5 parts by weight relative to 100 parts by weight of the absorbent resin particles, and more preferably 0.1 to 1 part by weight.

[0091] 2. Water-absorbing resin particles In the above-described method for manufacturing the absorbent resin particles of the present invention, by employing conditions preferred from the viewpoint of increasing the water retention capacity of physiological saline, the water absorption capacity of physiological saline under a load of 4.14 kPa, and the 5-minute value of DW without pressurization, absorbent resin particles with characteristics such as (A) to (C) can be suitably manufactured. For example, in the method for manufacturing absorbent resin particles, it is preferable to satisfy the storage modulus preferred in the first and second stages described above.

[0092] (A) The water retention capacity of physiological saline is above 50g / g and below 80g / g.

[0093] (B) The amount of physiological saline absorbed under a load of 4.14 kPa is more than 15 g / g and less than 40 g / g.

[0094] (C) The 5-minute value of DW without pressurization is above 50 mL / g and below 80 mL / g.

[0095] The water retention capacity of the (A) physiological saline in the absorbent resin particles of the present invention is preferably 50 g / g or more; furthermore, it is preferably 80 g / g or less, more preferably 70 g / g or less, and even more preferably 60 g / g or less; as a preferred range, 50 to 70 g / g is mentioned, and as a more preferred range, 50 to 60 g / g is mentioned, etc.

[0096] Furthermore, the saline water absorption capacity of the absorbent resin particles of the present invention under a load of (B) 4.14 kPa is preferably 15 g / g or more, more preferably 17 g / g or more, and even more preferably 19 g / g or more; it is also preferably 29 g / g or less, more preferably 27 g / g or less, even more preferably 25 g / g or less, and even more preferably 23 g / g or less; a preferred range is 15 to 29 g / g, and a more preferred range is 17 to 25 g / g, etc.

[0097] Furthermore, the 5-minute value of the unpressurized DW in (C) of the present invention is preferably 50 mL / g or more, more preferably 53 mL / g or more, even more preferably 55 mL / g or more, and particularly preferably 58 mL / g or more; in addition, it is preferably 78 mL / g or less, more preferably 73 mL / g or less, and even more preferably 68 mL / g or less; as a preferred range, 50 to 78 mL / g can be mentioned, and as a more preferred range, 58 to 68 mL / g can be mentioned, etc.

[0098] The saline water retention capacity, saline water absorption capacity under a 4.14 kPa load, and 5-minute DW value of the absorbent resin particles were determined using the methods described in the examples.

[0099] The saline water absorption capacity of the absorbent resin particles is preferably within the following ranges: Saline water absorption capacity is preferably 30 g / g or more, 35 g / g or more, 40 g / g or more, 45 g / g or more, 50 g / g or more, 55 g / g or more, or 60 g / g or more. Saline water absorption capacity is preferably 90 g / g or less, 85 g / g or less, 80 g / g or less, or 75 g / g or less. Saline water absorption capacity is preferably 30–90 g / g, more preferably 40–80 g / g, and even more preferably 60–75 g / g. The method for determining the saline water absorption capacity is described in detail in the examples described later.

[0100] The absorption rate of the physiological saline in the absorbent resin particles is preferably within the following ranges: Absorption rate is preferably 70 seconds or less, 60 seconds or less, 50 seconds or less, 45 seconds or less, or 40 seconds or less. Absorption rate is preferably 20 seconds or more, 25 seconds or more, or 30 seconds or more. Absorption rate is preferably 20 to 70 seconds, more preferably 25 to 60 seconds, and even more preferably 30 to 50 seconds. The absorption rate at room temperature (25 ± 2°C) can be used as the absorption rate. The method for measuring the absorption rate is described in detail in the examples described later.

[0101] The water-absorbing resin particles of the present invention are composed of a substance formed by cross-linking a polymer of a water-soluble olefinic unsaturated monomer, that is, a cross-linked polymer having structural units derived from the water-soluble olefinic unsaturated monomer.

[0102] The absorbent resin particles of the present invention are in the form of aggregates of fine particles (primary particles) (secondary particles). Examples of primary particle shapes include approximately spherical, irregularly broken, and plate-like shapes. The absorbent resin particles of the present invention, as secondary particles, can have various shapes. Examples of absorbent resin particle shapes include granular, approximately spherical, irregularly broken, plate-like, fibrous, flake-like, or aggregated forms of these resins. Preferably, the absorbent resin particles are granular, approximately spherical, irregularly broken, fibrous, or aggregated forms of these resins.

[0103] The median particle size of the water-absorbing resin particles is preferably 200. μ m or more, 250 μ m or more, 280 μ m or more, 300 μ m or above or 320 μ Above m. Furthermore, from the same perspective, the median particle size is preferably 700 μm. μ Below m, 600 μ Below m, 550 μ Below m, 500 μ Below m, 450 μ Below m or 400 μ The median particle size is less than 1 m. That is, the preferred median particle size is 200–700 μm. μ m, preferably 200–600 μ m, more preferably 250-500 μ m, more preferably 300–450 μ m, more preferably 320–400 μ m.

[0104] The median particle size of the water-absorbing resin particles can be determined using JIS standard sieves, specifically, by the method described in the examples.

[0105] 3. Absorbent materials The absorbent resin particles of the present invention constitute an absorbent material used in hygiene materials such as sanitary products and diapers, and are suitable for absorbent articles containing the above-mentioned absorbent material.

[0106] The absorbent of the present invention comprises the absorbent resin particles of the present invention. The absorbent may further comprise hydrophilic fibers. Examples of structures comprising the absorbent include sheet-like structures in which absorbent resin particles are fixed on or between multiple nonwoven fabrics; mixed dispersions obtained by mixing absorbent resin particles and hydrophilic fibers into a uniform composition; sandwich structures in which absorbent resin particles are sandwiched between layered hydrophilic fibers; and structures formed by wrapping absorbent resin particles and hydrophilic fibers in thin paper. It should be noted that other components may be incorporated into the absorbent, such as heat-melt synthetic fibers, heat-melt adhesives, adhesive emulsions, and other adhesive binders to improve the shape retention performance of the absorbent.

[0107] The absorbent resin particles in the absorbent body of this invention have a unit area weight of 50 g / m³. 2 Above and 400g / m 2 The following is a preferred weight per unit area: 100 g / m². 2 The above, more preferably 120g / m 2 The above is further optimized to 140g / m 2 The above; additionally, 300g / m³ is preferred. 2 The following is more preferably 250g / m 2 The following is a further preferred value: 200g / m 2 the following.

[0108] Examples of hydrophilic fibers include at least one selected from finely ground wood pulp, cotton, cotton linters, rayon, cellulose acetate, polyamide, polyester, and polyolefin. Examples include cellulose fibers such as cotton-like pulp, mechanical pulp, chemical pulp, and semi-chemical pulp obtained from wood; man-made cellulose fibers such as rayon and acetate rayon; and fibers containing synthetic resins such as polyamide, polyester, and polyolefin that have undergone hydrophilic treatment. The average fiber length of hydrophilic fibers is typically 0.1–10 mm, or 0.5–5 mm.

[0109] The hydrophilic fibers in the absorbent of this invention have a surface area weight of 50 g / m². 2 Above and 800g / m 2 The following is a preferred weight per unit area: 100 g / m². 2 The above, more preferably 120g / m 2 The above is further optimized to 140g / m 2 The above; additionally, 700g / m³ is preferred. 2 The following is more preferably 600g / m 2 The following is a further preferred value: 500g / m 2 the following.

[0110] The content of water-absorbing resin particles in the absorbent is preferably 5 to 100% by mass, more preferably 10 to 95% by mass, even more preferably 20 to 90% by mass, and even more preferably 30 to 80% by mass.

[0111] The absorbent article of the present invention can be manufactured by holding an absorbent body using the absorbent resin particles of the present invention between a liquid-permeable sheet (top sheet) and a liquid-impermeable sheet (back sheet). The liquid-permeable sheet is disposed on the side in contact with the body, and the liquid-impermeable sheet is disposed on the opposite side in contact with the body.

[0112] Examples of liquid-permeable sheets include hot-air type, spunbond type, chemically bonded type, and needle-punched type nonwoven fabrics containing fibers such as polyethylene, polypropylene, and polyester, as well as porous synthetic resin sheets. Examples of non-liquid-permeable sheets include synthetic resin films containing resins such as polyethylene, polypropylene, and polyvinyl chloride. The liquid-permeable sheet is preferably selected from at least one of the following groups: thermally bonded nonwoven fabric, hot-air type nonwoven fabric, spunbond nonwoven fabric, and spunbond / meltblown / spunbond nonwoven fabric.

[0113] The preferred weight per unit area of ​​the liquid-permeable sheet is 5 g / m². 2 Above and 100g / m 2 The following is more preferably 10g / m 2 Above and 60g / m 2Furthermore, to improve the diffusion of the liquid, embossing or perforation can be performed on the surface of the liquid-permeable sheet. These embossing or perforation processes can be carried out using known methods.

[0114] Examples of non-liquid-permeable sheets include: sheets containing synthetic resins such as polyethylene, polypropylene, and polyvinyl chloride; sheets containing nonwoven fabrics such as spunbond / meltblown / spunbond (SMS) nonwoven fabrics made by sandwiching water-resistant meltblown nonwoven fabric with high-strength spunbond nonwoven fabric; and sheets containing composite materials of these synthetic resins and nonwoven fabrics (e.g., spunbond nonwoven fabrics and spunlace nonwoven fabrics). Sheets containing synthetic resins primarily composed of low-density polyethylene (LDPE) resin can also be used as non-liquid-permeable sheets. For example, a non-liquid-permeable sheet may have a weight per unit area of ​​10–50 g / m². 2 Sheets containing synthetic resins.

[0115] The absorbent article preferably comprises: a laminate, a liquid-permeable sheet, and a liquid-impermeable sheet, wherein the laminate has an absorbent containing water-absorbing resin particles and a core-packing material sandwiching the absorbent between the upper and lower parts; the liquid-permeable sheet is disposed on the upper surface of the laminate; and the liquid-impermeable sheet is disposed on the side of the laminate opposite to the side of the liquid-permeable sheet.

[0116] 4. Additional Notes This specification includes at least the inventions shown in (1) to (14) below. (1) A method for manufacturing water-absorbing resin particles involves using a free radical polymerization initiator to induce reverse suspension polymerization of water-soluble olefinic unsaturated monomers to produce the water-absorbing resin particles. At least one of the free radical polymerization initiators is an azo compound. The reverse suspension polymerization has two or more polymerization processes. In the first stage of the polymerization process, (a) Use an internal crosslinking agent of more than 0.01 mmol and less than 0.11 mmol relative to 1 mol of water-soluble olefinic unsaturated monomer used in the first stage of polymerization; In the second stage of the polymerization process, (b) For every 1 mole of water-soluble olefinic unsaturated monomer used in the second stage of polymerization, use an internal crosslinking agent of 0 mmol to 0.042 mmol. (c) Use less than 0.38 mmol of an azo compound relative to 1 mole of water-soluble olefinic unsaturated monomer used in the second stage of polymerization; Following the polymerization process in the second stage, a surface crosslinking process is performed. (2) According to the method for manufacturing water-absorbing resin particles described in (1) above, in the polymerization process of the first stage, the amount of internal crosslinking agent used is 0.01 to 0.11 mmol, 0.02 to 0.09 mmol, 0.03 to 0.075 mmol, or 0.04 to 0.06 mmol, relative to 1 mol of water-soluble olefinic unsaturated monomer used in the polymerization of the first stage. (3) According to the method for manufacturing water-absorbing resin particles described in (1) or (2) above, in the polymerization process of the first stage, at least one of the free radical polymerization initiators used is an azo compound; relative to 1 mole of water-soluble olefinic unsaturated monomer used in the polymerization of the first stage, the amount of azo compound used is 0 to 1.0 mmol, 0 to 0.50 mmol, 0.10 to 0.38 mmol, or 0.20 to 0.35 mmol. (4) According to any one of the above (1) to (3) methods for manufacturing water-absorbing resin particles, in the second stage polymerization step, the amount of internal crosslinking agent used is 0 to 0.042 mmol, 0 to 0.038 mmol, 0 to 0.032 mmol, 0 to 0.030 mmol, or 0 to 0.025 mmol, relative to 1 mol of water-soluble olefinic unsaturated monomer used in the second stage polymerization. (5) According to any one of (1) to (4) above, in the method for manufacturing water-absorbing resin particles, in the second stage polymerization step, the amount of azo compound used is 0 to 0.38 mmol, 0 to 0.35 mmol, 0.05 to 0.35 mmol, or 0.10 to 0.35 mmol, relative to 1 mol of water-soluble olefinic unsaturated monomer used in the second stage polymerization. (6) According to any one of the above (1) to (5) methods for manufacturing water-absorbing resin particles, wherein the storage modulus of the 40-fold swollen gel formed by the primary particles obtained in the first stage polymerization process with ion-exchanged water is 10 Pa or more and 200 Pa or less. The storage modulus of the 40-fold swollen gel formed by the secondary particles obtained in the polymerization process after the second stage is above 5 Pa and below 200 Pa when ion-exchanged water is used. (7) According to any one of the above (1) to (6) methods for manufacturing water-absorbing resin particles, the storage modulus of the 40-fold swelling gel formed by ion-exchange water from the primary particles obtained in the first stage polymerization process is 15-150 Pa and 20-100 Pa. (8) According to any one of (1) to (7) above, in the method for manufacturing water-absorbing resin particles, the storage modulus of the 40-fold swelling gel formed by the secondary particles obtained in the second stage polymerization process with ion-exchanged water is 20-190 Pa, 20-170 Pa, 30-150 Pa, and 30-100 Pa. (9) A type of water-absorbing resin particle, which is a crosslinked polymer of a water-soluble olefinically unsaturated monomer. The absorbent resin particles have the following characteristics (A) to (C): (A) The water retention capacity of physiological saline is above 50g / g and below 80g / g.

[0126] (B) The amount of physiological saline absorbed under a load of 4.14 kPa is more than 15 g / g and less than 40 g / g.

[0127] (C) The 5-minute value of DW without pressurization is above 50 mL / g and below 80 mL / g. (10) According to the above (9) water-absorbing resin particles, the saline water retention capacity of the water-absorbing resin particles is 50-70 g / g and 50-60 g / g. (11) According to the above (9) or (10) water-absorbing resin particles, the water-absorbing capacity of the water-absorbing resin particles under a load of 4.14 kPa is 15-29 g / g and 17-25 g / g, respectively, for physiological saline. (12) The water-absorbing resin particles according to any one of (9) to (11) above, wherein the 5-minute unpressurized DW value of the water-absorbing resin particles is 50-78 mL / g and 58-68 mL / g. (13) The water-absorbing resin particles according to any one of (9) to (12) above, wherein the water-absorbing capacity of the water-absorbing resin particles for physiological saline is 40-80 g / g or 60-75 g / g. (14) The absorbent resin particles according to any one of (9) to (13) above, wherein the absorbent resin particles absorb physiological saline at a rate of 20 to 70 seconds, 25 to 60 seconds, or 30 to 50 seconds.

[0133] Example The present invention will now be described in detail with examples and comparative examples. However, the present invention is not limited to the examples.

[0134] <Manufacturing of Water-Absorbent Resin Particles> (Example 1) [First stage of polymerization process] A detachable cylindrical flask with an inner diameter of 11 cm and a volume of 2 L, equipped with stirring blades, was prepared as a reflux cooler, a dropping funnel, a nitrogen inlet pipe, and a stirrer. The stirring blades consist of two sections, each with four inclined blades with a blade diameter of 5 cm. In this flask, 293 g of n-heptane, used as a hydrocarbon dispersion medium, was added, along with 0.782 g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, HI-WAX 1105A), used as a polymeric dispersant. The mixture was stirred and heated to 80 °C to dissolve the dispersant, and then cooled to 50 °C.

[0135] In a 300 mL beaker, 92.0 g (1.03 mol) of an 80.5% by mass aqueous solution of acrylic acid, which is a water-soluble olefinic unsaturated monomer, was taken and 110.1 g of a 28% by mass aqueous solution of sodium hydroxide was added dropwise while cooling from the outside to neutralize it to 75 mol%. Then, 0.092 g (0.339 mmol) of 2,2′-azobis(2-amidinepropane) dihydrochloride, which is a water-soluble free radical polymerization initiator, 0.028 g (0.102 mmol) of potassium persulfate, 0.0101 g (0.058 mmol) of ethylene glycol diglycidyl ether, which is an internal crosslinking agent, and 37.2 g of deionized water were added and dissolved to prepare the monomer aqueous solution of the first stage.

[0136] Then, the aqueous solution prepared above was added to a separable flask, and after stirring for 10 minutes, a surfactant solution was further added, which was obtained by heating 7.45 g of n-heptane to dissolve 0.828 g of sucrose stearate (Mitsubishi Chemical Foods Co., Ltd., Ryoto Sugar Ester S-370) as a surfactant. While stirring at 500 rpm, the system was fully purged with nitrogen, and the flask was immersed in a 70°C water bath for 60 minutes to polymerize, thereby obtaining a first-stage polymerization slurry containing primary particles.

[0137] [Second stage polymerization process] In a 500 mL beaker, 128.8 g (1.44 mol) of an 80.5% by mass aqueous solution of acrylic acid, which is a water-soluble olefinic unsaturated monomer, was taken and 154.2 g of a 28% by mass aqueous solution of sodium hydroxide was added dropwise while cooling from the outside to neutralize it to 75 mol%. Then, 0.064 g (0.237 mmol) of 2,2′-azobis(2-amidinepropane) dihydrochloride, which is a water-soluble free radical polymerization initiator, 0.039 g (0.143 mmol) of potassium persulfate, and 6.49 g of deionized water were added and dissolved to prepare the monomer aqueous solution of the second stage.

[0138] While stirring at 1000 rpm, the internal temperature of the separable flask system was cooled to 25°C. Then, all of the second-stage aqueous solution was added to the first-stage polymerization slurry. The system was purged with nitrogen for 30 minutes, and then the flask was immersed again in a 70°C water bath for 60 minutes to allow for polymerization. Through these steps, the hydrogel resulting from the second-stage polymerization was obtained.

[0139] [Surface crosslinking] Then, the flask was immersed in an oil bath set at 125°C, and 176.6 g of water was discharged from the system through azeotropic distillation of n-heptane and water while the n-heptane was refluxed. Then, under stirring, 0.491 g of a 45% by mass aqueous solution of diethylenetriaminepentaacetic acid pentasodium and 2.58 g of a 3% by mass aqueous solution of sodium sulfite were added to the flask to obtain a second-stage polymerization slurry containing secondary particles.

[0140] Then, the flask was immersed again in an oil bath set at 125°C, and azeotropic distillation of n-heptane and water was performed, with the n-heptane being refluxed while 80.5 g (total 257.1 g) of water was further discharged from the system. Then, 5.52 g (0.634 μmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a surface crosslinking agent was added to the flask, and the mixture was kept at 83°C for 2 hours.

[0141] Then, the n-heptane is evaporated at 125°C to dry it, thereby obtaining a dried product. This dried product is then passed through a mesh of 850 μm. μ A sieve was used to sieve a sample containing 0.2% by mass of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) relative to the dried product, yielding 235.2 g of absorbent resin particles. The median particle size of the absorbent resin particles was 347 μm. μ m.

[0142] The physiological saline water absorption capacity of the water-absorbing resin particles in Example 1 was 64 g / g, and the water absorption rate of the water-absorbing resin particles was 35 seconds.

[0143] (Example 2) The amount of water discharged from the system via the second azeotropic distillation was changed to 90.2 g (total 266.8 g); otherwise, 223.4 g of water-absorbing resin particles were obtained in the same manner as in Example 1. The median particle size of the water-absorbing resin particles was 339 μm. μ m.

[0144] The physiological saline water absorption capacity of the water-absorbing resin particles in Example 2 was 72 g / g, and the water absorption rate of the water-absorbing resin particles was 33 seconds.

[0145] (Example 3) The amount of 2,2′-azobis(2-amidinylpropane) dihydrochloride added to the monomer aqueous solution in the second stage was changed to 0.129 g (0.475 mmol), the amount of ion-exchanged water added was changed to 6.42 g, and the amount of water discharged from the system by the second azeotropic distillation was changed to 80.3 g (total 256.9 g); otherwise, 226.0 g of water-absorbing resin particles were obtained in the same manner as in Example 1. The median particle size of the water-absorbing resin particles was 353 μm. μ m.

[0146] The physiological saline water absorption capacity of the water-absorbing resin particles in Example 3 was 71 g / g, and the water absorption rate of the water-absorbing resin particles was 39 seconds.

[0147] (Example 4) In the second stage, 0.0052 g (0.030 mmol) of ethylene glycol diglycidyl ether was added as an internal crosslinking agent to the monomer aqueous solution. The amount of ion-exchanged water added to the monomer aqueous solution in the second stage was changed to 6.48 g, and the amount of water discharged from the system by the second azeotropic distillation was changed to 83.9 g (total 260.6 g). Otherwise, 224.3 g of water-absorbing resin particles were obtained in the same manner as in Example 1. The median particle size of the water-absorbing resin particles was 361 μm. μ m.

[0148] The physiological saline water absorption capacity of the water-absorbing resin particles in Example 4 was 68 g / g, and the water absorption rate of the water-absorbing resin particles was 39 seconds.

[0149] (Example 5) The amount of water discharged from the system via the second azeotropic distillation was changed to 89.9 g (total 266.5 g), and the amount of 2% by mass ethylene glycol diglycidyl ether aqueous solution added was changed to 8.28 g (0.951 μmol); otherwise, 225.7 g of water-absorbing resin particles were obtained in the same manner as in Example 1. The median particle size of the water-absorbing resin particles was 360 μm. μ m.

[0150] The physiological saline water absorption capacity of the water-absorbing resin particles in Example 5 was 72 g / g, and the water absorption rate of the water-absorbing resin particles was 40 seconds.

[0151] (Example 6) 0.0129 g (0.122 mmol) of sodium hypophosphite as a chain transfer agent was added to the monomer aqueous solution in the second stage. The amount of ion-exchanged water added to the monomer aqueous solution in the second stage was changed to 6.47 g, and the amount of water discharged from the system by the second azeotropic distillation was changed to 82.9 g (total 259.5 g). Otherwise, 221.5 g of water-absorbing resin particles were obtained in the same manner as in Example 1. The median particle size of the water-absorbing resin particles was 369 μm. μ m.

[0152] The physiological saline water absorption capacity of the water-absorbing resin particles in Example 6 was 64 g / g, and the water absorption rate of the water-absorbing resin particles was 37 seconds.

[0153] (Example 7) The amount of ethylene glycol diglycidyl ether added to the monomer aqueous solution in the first stage was changed to 0.0184 g (0.106 μmol), and the amount of water discharged from the system by the second azeotropic distillation was changed to 84.7 g (total 261.4 g); otherwise, 220.1 g of water-absorbing resin particles were obtained in the same manner as in Example 1. The median particle size of the water-absorbing resin particles was 423 μm. μ m.

[0154] The physiological saline water absorption capacity of the water-absorbing resin particles in Example 7 was 67 g / g, and the water absorption rate of the water-absorbing resin particles was 48 seconds.

[0155] (Example 8) [First stage of polymerization process] A detachable cylindrical flask with an inner diameter of 11 cm and a volume of 2 L, equipped with stirring blades, was prepared as a reflux cooler, a dropping funnel, a nitrogen inlet pipe, and a stirrer. The stirring blades consist of two sections, each with four inclined blades with a blade diameter of 5 cm. In this flask, 294 g of n-heptane, used as a hydrocarbon dispersion medium, was added, along with 0.644 g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, HI-WAX 1105A), used as a polymeric dispersant. The mixture was stirred and heated to 80 °C to dissolve the dispersant, and then cooled to 50 °C.

[0156] In a 300 mL beaker, 92.0 g (1.03 mol) of an 80.5% by mass aqueous solution of acrylic acid, which is a water-soluble olefinic unsaturated monomer, was taken. While cooling from the outside, 110.1 g of a 28% by mass aqueous solution of sodium hydroxide was added dropwise to neutralize it to 75 mol%. Then, 0.074 g (0.272 μmol) of potassium persulfate, which is a water-soluble free radical polymerization initiator, 0.0046 g (0.026 μmol) of ethylene glycol diglycidyl ether, which is an internal crosslinking agent, and 37.3 g of deionized water were added and dissolved to prepare the monomer aqueous solution of the first stage.

[0157] Then, the aqueous solution prepared above was added to a separable flask, and after stirring for 10 minutes, a surfactant solution was further added, which was obtained by heating 5.8 g of n-heptane to dissolve 0.644 g of sucrose stearate (Mitsubishi Chemical Foods Co., Ltd., Ryoto Sugar Ester S-370) as a surfactant. While stirring at 500 rpm, the system was fully purged with nitrogen, and the flask was immersed in a 70°C water bath for 60 minutes to polymerize, thereby obtaining a first-stage polymerization slurry containing primary particles.

[0158] [Second stage polymerization process] In a 500 mL beaker, 128.8 g (1.44 mol) of an 80.5% by mass aqueous solution of acrylic acid, which is a water-soluble olefinic unsaturated monomer, was taken and 154.2 g of a 28% by mass aqueous solution of sodium hydroxide was added dropwise while cooling from the outside to neutralize it to 75 mol%. Then, 0.064 g (0.237 mmol) of 2,2′-azobis(2-amidinepropane) dihydrochloride, which is a water-soluble free radical polymerization initiator, 0.039 g (0.143 mmol) of potassium persulfate, and 6.49 g of deionized water were added and dissolved to prepare the monomer aqueous solution of the second stage.

[0159] While stirring at 1000 rpm, the separable flask system was cooled to 25°C. Then, the entire aqueous solution from the second stage was added to the polymerization slurry from the first stage. The system was purged with nitrogen for 30 minutes, and then the flask was immersed again in a 70°C water bath for 60 minutes to allow for polymerization. Through these steps, the hydrogel resulting from the second stage of polymerization was obtained.

[0160] [Surface crosslinking] Then, the flask was immersed in an oil bath set at 125°C, and 176.6 g of water was discharged from the system through azeotropic distillation of n-heptane and water while the n-heptane was refluxed. Then, under stirring, 0.491 g of a 45% by mass aqueous solution of diethylenetriaminepentaacetic acid pentasodium and 2.58 g of a 3% by mass aqueous solution of sodium sulfite were added to the flask to obtain a second-stage polymerization slurry containing secondary particles.

[0161] Then, the flask was immersed again in an oil bath set at 125°C, and azeotropic distillation of n-heptane and water was performed, with the n-heptane being refluxed while 79.7 g (total 256.4 g) of water was further discharged from the system. Then, 5.52 g (0.634 μmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a surface crosslinking agent was added to the flask, and the mixture was kept at 83°C for 2 hours.

[0162] Then, the n-heptane is evaporated at 125°C to dry it, thereby obtaining a dried product. This dried product is then passed through a mesh of 850 μm. μ A sieve was used to sieve a sample containing 0.2% by mass of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) relative to the dried product, yielding 214.9 g of absorbent resin particles. The median particle size of the absorbent resin particles was 372 μm. μ m.

[0163] The physiological saline water absorption capacity of the water-absorbing resin particles in Example 8 was 73 g / g, and the water absorption rate of the water-absorbing resin particles was 41 seconds.

[0164] (Comparative Example 1) In the second stage, 2,2′-azobis(2-amidinylpropane) dihydrochloride was not added to the monomer aqueous solution. The amount of potassium persulfate added to the second stage monomer aqueous solution was changed to 0.090 g (0.334 mmol), and 0.0116 g (0.067 mmol) of ethylene glycol diglycidyl ether was added. The amount of water discharged from the system by the second azeotropic distillation was changed to 95.4 g (total 272.0 g). Otherwise, 224.4 g of water-absorbing resin particles were obtained in the same manner as in Example 8. The median particle size of the water-absorbing resin particles was 347 μm. μ m.

[0165] The saline water absorption capacity of the hydrosorbent resin particles in Comparative Example 1 was 67 g / g, and the water absorption rate of the hydrosorbent resin particles was 39 seconds.

[0166] (Comparative Example 2) [First stage of polymerization process] A round-bottomed cylindrical separable flask with an inner diameter of 11 cm and a volume of 2 L, equipped with stirring blades, was prepared as a reflux cooler, a dropping funnel, a nitrogen inlet pipe, and a stirrer. The stirring blades have two sections, each with four inclined blades with a blade diameter of 5 cm. In this flask, 265 g of n-heptane, used as a hydrocarbon dispersion medium, was added, along with 0.736 g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, HI-WAX 1105A), used as a polymeric dispersant. The mixture was stirred and heated to 80 °C to dissolve the dispersant, and then cooled to 50 °C.

[0167] In a 300 mL beaker, 92.0 g (1.03 mol) of an 80.5% by mass aqueous solution of acrylic acid, a water-soluble olefinic unsaturated monomer, was taken and added dropwise with 110.1 g of a 28% by mass aqueous solution of sodium hydroxide while cooling from the outside, to neutralize to 75 mol%. Then, 0.092 g (0.339 mmol) of hydroxyethyl cellulose (Sumitomo Seika Co., Ltd., HEC AW-15F) as a thickener, 0.092 g (0.339 mmol) of 2,2′-azobis(2-amidinepropane) dihydrochloride as a water-soluble free radical polymerization initiator, 0.028 g (0.102 mmol) of potassium persulfate, 0.0046 g (0.026 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent, and 14.3 g of deionized water were added and dissolved to prepare the monomer aqueous solution of the first stage.

[0168] Then, the aqueous solution prepared above was added to a separable flask, and after stirring for 10 minutes, a surfactant solution was further added, which was obtained by heating 6.62 g of n-heptane to dissolve 0.736 g of sucrose stearate (Mitsubishi Chemical Foods Co., Ltd., Ryoto Sugar Ester S-370) as a surfactant. While stirring at 600 rpm, the system was fully purged with nitrogen, and the flask was immersed in a 70°C water bath for 60 minutes to polymerize, thereby obtaining a first-stage polymerization slurry containing primary particles.

[0169] [Second stage polymerization process] In a 500 mL beaker, 128.8 g (1.44 mol) of an 80.5% by mass aqueous solution of acrylic acid, which is a water-soluble olefinic unsaturated monomer, was taken and 154.2 g (75 mol) of a 28% by mass aqueous solution of sodium hydroxide was added dropwise while cooling from the outside to neutralize it to 75 mol%. Then, 0.129 g (0.475 mmol) of 2,2′-azobis(2-amidinepropane) dihydrochloride, which is a water-soluble free radical polymerization initiator, 0.039 g (0.143 mmol) of potassium persulfate, 0.0116 g (0.067 mmol) of ethylene glycol diglycidyl ether, which is an internal crosslinking agent, and 6.41 g of deionized water were added and dissolved to prepare the monomer aqueous solution of the second stage.

[0170] While stirring at 1000 rpm, the separable flask system was cooled to 25°C. Then, the entire aqueous solution from the second stage was added to the polymerization slurry from the first stage. The system was purged with nitrogen for 30 minutes, and then the flask was immersed again in a 70°C water bath for 60 minutes to allow for polymerization. Through these steps, the hydrogel resulting from the second stage of polymerization was obtained.

[0171] [Surface crosslinking] Then, the flask was immersed in an oil bath set at 125°C, and 176.6 g of water was discharged from the system through azeotropic distillation of n-heptane and water while the n-heptane was refluxed. Then, under stirring, 0.393 g of a 45% by mass aqueous solution of diethylenetriaminepentaacetic acid pentasodium and 4.42 g of a 3% by mass aqueous solution of sodium sulfite were added to the flask to obtain a second-stage polymerization slurry containing secondary particles.

[0172] Then, the flask was immersed again in an oil bath set to 125°C, and 49.3 g (total 226.0 g) of water was further discharged from the system by azeotropic distillation of n-heptane and water, while the n-heptane was refluxed. Then, 4.42 g (0.507 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a surface crosslinking agent was added to the flask, and the mixture was kept at 83°C for 2 hours.

[0173] Then, the n-heptane is evaporated at 125°C to dry it, thereby obtaining a dried product. This dried product is then passed through a mesh of 850 μm. μ A sieve was used to sieve a sample containing 0.2% by mass of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) relative to the dried product, yielding 229.4 g of absorbent resin particles. The median particle size of the absorbent resin particles was 352 μm. μ m.

[0174] The saline water absorption capacity of the superabsorbent resin particles in Comparative Example 2 was 66 g / g, and the water absorption rate of the superabsorbent resin particles was 36 seconds.

[0175] [Determination of the storage modulus of primary particles (40-fold swollen gel formed with ion-exchanged water)] In the manufacture of water-absorbing resin particles, a first-stage polymerization slurry is obtained. The reaction solution is then heated in an oil bath at 125°C, and subjected to azeotropic distillation of n-heptane and water, with the n-heptane refluxed while water is drained from the system until the internal temperature reaches 88°C. The n-heptane is then evaporated at 125°C to dry the product, thus obtaining a dried product. This dried product is then passed through an 850-mesh screen. μ Using a sieve of m, 0.2% by mass of amorphous silica (OrientalSilicas Corporation, Tokusil NP-S) was mixed with the dried product to obtain primary particles.

[0176] Next, the primary particles were swollen 40 times using ion-exchanged water to prepare a 40-fold swollen gel. Specifically, first, 195.0 g of ion-exchanged water was measured into a 500 mL beaker. Then, the beaker containing the ion-exchanged water was placed in a MIYAMOTO CORPORATION jar tester (MJS-8S), and a stirring blade with a stainless steel flat blade (7 cm horizontal length × 2.5 cm vertical length × 0.1 cm thickness) was attached, positioned 0.5 cm above the bottom of the beaker, and rotated at 500 rpm. Next, 5.0 g of primary particles were added to the stirring beaker without clumping. One minute after addition, the rotation speed was changed to 300 rpm, and stirring continued for one hour to prepare a 40-fold swollen gel. The 40-fold swollen gel was transferred to a centrifuge tube and centrifuged at 2000 rpm for 10 minutes using a centrifuge (manufactured by a domestic centrifuge company, product number H-36) to degas the gel and prepare the test sample.

[0177] The storage modulus was determined using a stress-controlled rheometer (manufactured by TA Instruments Ltd, product number AR2000ex) via creep measurement. The measurement temperature was 25°C, and the fixture used was a 60mm diameter aluminum parallel plate (manufactured by TA Instruments Ltd, product number 513600.901). Shear stress was measured at 0.7 Pa.

[0178] Using a 15mL measuring spoon, measure the test sample and place it on the test stage without introducing air bubbles. Lower the clamp until the lower part of the clamp is filled with the test sample, ensuring a 4000mm gap between the clamp and the test stage. μm. The sample exposed on the outside of the fixture was removed. Creep measurements were performed, and the storage modulus was calculated using Jeffreys underdamped ringing analysis. The results are shown in Table 1.

[0179] [Determination of the storage modulus of secondary particles (40-fold swollen gel formed with ion-exchanged water)] In the manufacture of water-absorbing resin particles, a second-stage polymerization slurry is obtained. The reaction solution is then heated in an oil bath at 125°C, and subjected to azeotropic distillation of n-heptane and water, with the n-heptane refluxed while water is drained from the system until the internal temperature reaches 88°C. The n-heptane is then evaporated at 125°C to dry the product, thus obtaining a dried product. This dried product is then passed through an 850-mesh screen. μ The sample was sieved through a m-sieve and mixed with 0.2% by mass of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) relative to the dried sample to obtain secondary particles. The storage modulus was then determined using the same method as for the primary particles. The results are shown in Table 1.

[0180] [Water retention capacity of physiological saline] A cotton bag (cotton broad, size 60, 100mm wide x 200mm long) containing 2.0g of absorbent resin granules was placed in a 500mL beaker. 500g of 0.9% sodium chloride aqueous solution (physiological saline) was added to the cotton bag without clumping, and the top of the bag was secured with a rubber band. The bag was left to stand for 30 minutes to allow the absorbent resin granules to swell. After 30 minutes, the cotton bag was dehydrated for 1 minute using a dehydrator (manufactured by Kokusan Co., Ltd., product number: H-122) set to a centrifugal force of 167G. The mass Wa (g) of the cotton bag containing the swollen gel after dehydration was measured. The same procedure was performed without adding absorbent resin granules, and the empty mass Wb (g) of the wet cotton bag was measured. The water retention capacity of the physiological saline was calculated using the following formula. The results are shown in Table 1.

[0181] The water retention capacity of physiological saline (g / g) = [Wa - Wb] / 2.0 [5-minute values ​​for unpressurized DW] 5-minute value of unpressurized DW for water-absorbing resin particles Figure 1 The measurement was performed using the apparatus shown. The measurement was conducted five times on a water-absorbing resin particle, and the average of the three measured values ​​after removing the lowest and highest values ​​was calculated.

[0182] The measuring apparatus comprises a burette section 1, a conduit 5, a measuring stage 13, a nylon mesh 15, a stand 11, and a clamp 3. The burette section 1 includes: a graduated burette 21, a rubber stopper 23 that seals the opening at the top of the burette 21, a stopcock 22 connected to the lower front end of the burette 21, an air inlet tube 25 connected to the lower part of the burette 21, and a stopcock 24. The burette section 1 is fixed by the clamp 3. The flat measuring stage 13 has a through hole 13a with a diameter of 2 mm formed in its center and is supported by a height-variable stand 11. The through hole 13a of the measuring stage 13 is connected to the stopcock 22 of the burette section 1 via the conduit 5. The inner diameter of the conduit 5 is 6 mm.

[0183] First, close stopcocks 22 and 24 of burette section 1, and inject 0.9% saline solution 50, adjusted to 25°C, into burette 21 through the opening at the top. The concentration of the saline solution is 0.9% by mass, based on the mass of the saline solution. After sealing the opening of burette 21 with rubber stopper 23, open stopcocks 22 and 24. Fill the tube 5 with 0.9% saline solution 50, ensuring no air bubbles enter. Adjust the height of the measuring stage 13 so that the water level of the 0.9% saline solution in the through hole 13a is the same as the height of the upper surface of the measuring stage 13. After adjustment, read the water level of the 0.9% saline solution 50 in burette 21 using the scale, and take this position as the zero point (the reading at 0 seconds).

[0184] A nylon mesh 15 (100mm × 100mm, 250 mesh, approximately 50mm thick) is laid near the through hole 13a on the measuring platform 13. μ A cylinder with an inner diameter of 30 mm and a height of 20 mm was placed in the center of the nylon mesh 15. 1.00 g of absorbent resin particles 10a were evenly distributed within the cylinder. The cylinder was then carefully removed, yielding a sample with the absorbent resin particles 10a dispersed in a circular pattern in the center of the nylon mesh 15. Next, the nylon mesh 15 containing the absorbent resin particles 10a was moved rapidly to a position where its center would reach the through-hole 13a, without causing the absorbent resin particles 10a to disperse, and the measurement was initiated. The moment when the air bubble was initially introduced from the air inlet tube 25 into the burette 21 was defined as the start of absorption (0 seconds).

[0185] The decrease in 0.9% saline solution 50 in burette 21 was recorded sequentially in 0.1 mL units (i.e., the amount of 0.9% saline solution absorbed by the absorbent resin particles 10a). The decrease in 0.9% saline solution 50, Wc (mL), was recorded 5 minutes after the start of water absorption by the absorbent resin particles 10a. Based on Wc, the 5-minute unpressurized DW value was calculated using the following formula. Unpressurized DW is the amount of water absorbed by each 1.00 g of absorbent resin particles 10a. The results are shown in Table 1.

[0186] The 5-minute DW value (mL / g) without pressurization = Wc / 1.00 [Water absorption under 4.14 kPa load] use Figure 2 The apparatus schematically shown in the diagram measures the amount of water absorbed by absorbent resin particles with physiological saline under a load of 4.14 kPa (water absorption under 4.14 kPa load). The water absorption of one type of absorbent resin particle was measured twice under the load, and the average value was calculated. Figure 2 The apparatus comprises a burette section 1, a clamp 3, a conduit 5, a stand 11, a measuring stage 13, and a measuring part 4 placed on the measuring stage 13. The burette section 1 includes: a graduated burette 21, a rubber stopper 23 that seals the opening at the top of the burette 21, a stopcock 22 connected to the lower front end of the burette 21, an air inlet tube 25 connected to the lower part of the burette 21, and a stopcock 24. The burette section 1 is fixed by the clamp 3. The flat measuring stage 13 has a through hole 13a with a diameter of 2 mm formed in its center and is supported by a height-variable stand 11. The through hole 13a of the measuring stage 13 is connected to the stopcock 22 of the burette section 1 via the conduit 5. The inner diameter of the conduit 5 is 6 mm.

[0187] The measuring unit 4 includes: an acrylic resin cylinder 31, a polyamide mesh 32 bonded to one opening of the cylinder 31, and a weight 33 movable vertically inside the cylinder 31. The cylinder 31 is placed on the measuring stage 13 via the polyamide mesh 32. The inner diameter of the cylinder 31 is 20 mm. The mesh size of the polyamide mesh 32 is 75. μ m (200 mesh). The weight 33 has a diameter of 19 mm and a mass of 119.6 g, and as described later, it is able to apply a load of 4.14 kPa to the water-absorbing resin particles 10a uniformly arranged on the polyamide mesh 32.

[0188] First, close stopcocks 22 and 24 of burette section 1, and inject 0.9% saline solution (adjusted to 25°C) into burette 21 through the opening at the top. Next, after sealing the top opening of burette 21 with rubber stopper 23, open stopcocks 22 and 24. Fill the tube 5 with 0.9% saline solution 50, ensuring no air bubbles enter. Adjust the height of the measuring stage 13 so that the water level of the 0.9% saline solution in the through-hole 13a is the same as the height of the upper surface of the measuring stage 13. After adjustment, read the water level of the 0.9% saline solution 50 in burette 21 using the scale, and take this position as the zero point (the reading at 0 seconds).

[0189] In the measuring unit 4, 0.10 g of absorbent resin particles 10a are uniformly arranged on a polyamide mesh 32 inside the cylinder 31. A weight 33 is placed on the absorbent resin particles 10a. The cylinder 31 is positioned with its center aligned with the conduit opening at the center of the measuring stage 13. The decrease in saline in the burette 21 (i.e., the amount of saline absorbed by the absorbent resin particles 10a) Wd (mL) is recorded 60 minutes after the absorbent resin particles 10a begin absorbing saline from the conduit 5. The amount of saline absorbed by the absorbent resin particles 10a under a load of 4.14 kPa is calculated using the following formula. The results are shown in Table 1.

[0190] 4.14 kPa load, saline water absorption (g / g) = Wd (mL) × 1.0028 [g / mL] (specific gravity of saline) / 0.10 [Water absorption capacity of physiological saline] 500 g of 0.9% physiological saline was measured into a 500 mL beaker. Then, 2.0 g of absorbent resin particles were dispersed in the saline solution in a non-clumping manner while stirring at 600 rpm with a magnetic stir bar (8 mm φ × 30 mm length, without rings). The mixture was left to stand for 60 minutes with stirring to allow the particles to fully swell, thus obtaining a dispersion containing a swollen gel. Next, the mesh size (75) was measured. μ After determining the mass We[g] of the standard sieve, the above dispersion is passed through the standard sieve. Then, the sieve is placed at an angle of about 30 degrees relative to the horizontal for 30 minutes to remove the remaining water. The mass Wf[g] of the sieve with residual swollen gel is measured, and the amount of water absorbed by the physiological saline Wg[g / g] is calculated using the following formula.

[0191] The amount of water absorbed by physiological saline, Wg [g / g], is calculated as follows: (Wf - We) / 2.0 [Median Particle Size] 50g of water-absorbing resin granules were used for median particle size determination. Starting from the top, the granules were arranged in sequence according to a mesh size of 710. μ sieve with 600 mesh size μ sieve with 500 mesh size μ sieve with a mesh size of 425 m μ sieve with 300 mesh size μ sieve with 250 mesh size μ sieve with 150 mesh size μA JIS standard sieve is assembled in sequence with a sieve and a receiving tray. Water-absorbing resin particles are placed in the top sieve of the assembly and shaken for 20 minutes using a Ro-Tap shaker for grading. After grading, the mass percentage of water-absorbing resin particles remaining on each sieve relative to the total mass is calculated to determine the particle size distribution. Regarding this particle size distribution, the material remaining on the sieves is accumulated sequentially from the side with the largest particle size. The relationship between the sieve mesh size and the cumulative mass percentage of water-absorbing resin particles remaining on the sieves is plotted on logarithmic probability paper. By connecting the plotted points on the probability paper with a straight line, the particle size corresponding to 50% of the cumulative mass percentage is taken as the median particle size.

[0192] [Water absorption rate (Vortex method)] The water absorption rate of superabsorbent resin particles to physiological saline was determined using the eddy current method as follows: First, 50±0.1g of physiological saline, adjusted to a temperature of 25±0.2℃, was measured into a 100mL beaker in a constant temperature water bath. Next, a magnetic stir bar (8mmφ×30mm, ringless) was used to stir the solution at 600rpm, thereby generating an eddy current. 2.0±0.002g of superabsorbent resin particles were added to the physiological saline in a single addition. The time [in seconds] from the addition of the superabsorbent resin particles to the convergence of the eddy current at the liquid surface was measured and recorded as the water absorption rate of the superabsorbent resin particles.

[0193] [Table 1]

[0194] Explanation of reference numerals in the attached figures 1. Burette Section 3. Fixture 4. Measurement Section 5 catheters 10a water-absorbing resin particles 11 racks 13 Measuring Platform 13a Through hole 15 Nylon mesh 21 Burette 22. Cocktail 23 Rubber stoppers 24. Cocktail 25 Air inlet tube 31. Cylinder 32 Polyamide mesh 33 heavy objects 50g salt water.

Claims

1. A method for manufacturing water-absorbing resin particles, characterized in that, This invention relates to a method for manufacturing water-absorbing resin particles by using a free radical polymerization initiator to induce reverse suspension polymerization of water-soluble olefinically unsaturated monomers. At least one of the free radical polymerization initiators is an azo compound. The reverse suspension polymerization has two or more polymerization processes. In the first stage of the polymerization process, (a) Use an internal crosslinking agent of more than 0.01 mmol and less than 0.11 mmol relative to 1 mol of water-soluble olefinic unsaturated monomer used in the first stage of polymerization; In the second stage of the polymerization process, (b) For every 1 mole of water-soluble olefinic unsaturated monomer used in the second stage of polymerization, use an internal crosslinking agent of 0 mmol to 0.042 mmol. (c) Use less than 0.38 mmol of an azo compound relative to 1 mole of water-soluble olefinic unsaturated monomer used in the second stage of polymerization; Following the polymerization process after the second stage, a surface crosslinking process is performed.

2. The method for manufacturing water-absorbing resin particles according to claim 1, wherein, The storage modulus of the 40-fold swollen gel formed by deionized water from the primary particles obtained in the first stage of polymerization is above 10 Pa and below 200 Pa. The storage modulus of the 40-fold swollen gel formed by the secondary particles obtained in the polymerization process after the second stage is above 5 Pa and below 200 Pa when ion-exchanged water is used.

3. The method for manufacturing water-absorbing resin particles according to claim 1 or 2, wherein, The absorbent resin particles have the following characteristics (A) to (C): (A) The water retention capacity of physiological saline is above 50g / g and below 80g / g. (B) The saline water absorption under a load of 4.14 kPa is above 15 g / g and below 40 g / g. (C) The 5-minute value of DW without pressurization is above 50 mL / g and below 80 mL / g.

4. A water-absorbing resin particle, characterized in that, Crosslinked polymers of water-soluble olefinically unsaturated monomers. The absorbent resin particles have the following characteristics (A) to (C): (A) The water retention capacity of physiological saline is above 50g / g and below 80g / g. (B) The saline water absorption under a load of 4.14 kPa is above 15 g / g and below 40 g / g. (C) The 5-minute value of DW without pressurization is above 50 mL / g and below 80 mL / g.

5. An absorber, characterized in that, It includes the water-absorbing resin particles as described in claim 4.

6. An absorbent article, characterized in that, It includes the absorber as described in claim 5.

Citation Information

Patent Citations

  • Production of water absorbing resin

    JP1991227301A

Cited By

  • Preparation method of water-absorbent resin

    CN121270758A